Voting at the political fault line : California's experiment with the blanket primary - Cain, Bruce E.; Gerber, Elisabeth R., 1964- (University of California Press, 2002)
California's adoption of the blanket primary in 1996 presented a unique natural experiment on the impact that election rules have on politics. Billed as a measure that would increase voter participation and end ideological polarization, Proposition 198 placed California voters once again on the frontier of political reform.
"Published in association with the Institute of Governmental Studies."
Keywords: Primaries -- California.; Élections primaires -- Californie.; POLITICAL SCIENCE -- Political Process -- Political Parties.; HISTORY -- United States -- State & Local -- West (AK, CA, CO, HI, ID, MT, NV, UT, WY); Primaries; California